The Effectiveness of Using Augmented Reality to Improve Young Learners’ English Vocabulary Mastery - Rahmadani, Nabila Putri; Saputri, Tiyas; Basuki, Edi Pujo; Djuwari, Djuwari (Jurnal Pendidikan Anak, 2024)
This research was conducted to examine the effectiveness of using Augmented Reality to improve young learners’ English vocabulary mastery and to find out the students’ perceptions after using Augmented Reality as a learning medium at one of elementary schools in Surabaya. This quantitative research used experimental design involving experimental and control groups. The data collected using pre-test, post-test and questionnaire. The results of the students' pre-test and post-test were analyzed using the independent sample t-test, and the results of the questionnaire data were collected from the students by questionnaire sheet. The result indicated that Augmented Reality effectively improved young learners' English vocabulary mastery with the mean scores in the experimental group increased notably from 37,6133 in the pre-test to 75,4000 in the post-test. According to the data of questionnaire, the students mostly agreed that their scores were improved because Augmented Reality offered interesting and enjoyable learning experience. This was an indication that using Augmented Reality not only significantly boosts vocabulary scores but also positively impacts students' perceptions of the learning process.